Single-Mother Families in Eight Countries: Economic Status and Social Policy - Ying-Ling Irene Wong; Sara McLanahan; Irwin Garfinkel (Luxembourg Income Study (LIS), 1992)
A study comparing economic status of single mother families to each other and two parent families in eight countries, using data from the LIS. Four hypotheses are investigated and findings are reported.
Keywords: 330